2024
DOI: 10.1111/jce.16183
|View full text |Cite
|
Sign up to set email alerts
|

Caudal fluoroscopic guidance for the insertion of transvenous pacing leads

Matthew B. Morton,
Jeremy William,
Peter M. Kistler
et al.

Abstract: BackgroundPneumothorax is a well‐recognized complication of cardiac implantable electronic device (CIED) insertion. While AP fluoroscopy alone is the most commonly imaging technique for subclavian or axillary access, caudal fluoroscopy (angle 40°) is routinely used at our institution. The caudal view provides additional separation of the first rib and clavicle and may reduce the risk of pneumothorax. We assessed outcomes at our institution of AP and caudal fluoroscopic guided pacing lead insertion.MethodsRetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…6 In this issue of Journal of Cardiovascular Electrophysiology, Morton et al describe a large, single-center retrospective analysis of employing caudal 40°angulation rather than conventional antero-posterior (AP) fluoroscopy to guide subclavian vein puncture for insertion of transvenous pacing wires for CIEDs that demonstrates a reduction in pneumothorax rates and use of contrast venography. 7 Although the most employed imaging technique for subclavian vein puncture is straight AP fluoroscopy, the method of adding 40°caudal angulation to standard fluoroscopy was described by Yang et al and suggested reductions in pneumothorax rates by affording the operator a measure of needle depth in relation to important structures such as the pleural space, improving safety. 8 Specifically, the anterior surface of the lung can be better appreciated in this oblique view, and there is greater separation between the clavicle and the first rib, the space through which the puncture needle is advanced to cannulate the subclavian vein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 In this issue of Journal of Cardiovascular Electrophysiology, Morton et al describe a large, single-center retrospective analysis of employing caudal 40°angulation rather than conventional antero-posterior (AP) fluoroscopy to guide subclavian vein puncture for insertion of transvenous pacing wires for CIEDs that demonstrates a reduction in pneumothorax rates and use of contrast venography. 7 Although the most employed imaging technique for subclavian vein puncture is straight AP fluoroscopy, the method of adding 40°caudal angulation to standard fluoroscopy was described by Yang et al and suggested reductions in pneumothorax rates by affording the operator a measure of needle depth in relation to important structures such as the pleural space, improving safety. 8 Specifically, the anterior surface of the lung can be better appreciated in this oblique view, and there is greater separation between the clavicle and the first rib, the space through which the puncture needle is advanced to cannulate the subclavian vein.…”
mentioning
confidence: 99%
“…In the current paper, although overall complication rates were low, 40°caudal angulation was associated with a 72% lower risk of pneumothorax than AP fluoroscopy, and interestingly, a reduced requirement for contrast venography. 7 A large number of cases were included, totaling 3252 patients (2536 using the caudal technique, and 716 using AP guidance alone), which is a key strength for this paper. The mean age was 71.1 years and 66.7% of patients were male, which is similar to previously published cohorts, and proceduralist experience did not differ significantly between groups.…”
mentioning
confidence: 99%